Kinetics of Porang (Amorphophallus oncophyllus) Chips during Storage at Various Temperatures - Munawwaroh, Fajriyah Dian; Rahayoe, Sri; Bintoro, Nursigit (agriTECH, 2025)
Porang chips are dried food products that easily absorb moisture from storage environment. This highlights the need for storing porang chips under appropriate environmental conditions to maintain quality by controlling temperatures and humidity of storage area. Therefore, this study aimed to assess quality characteristics of porang chips by analyzing the rate of change using the kinetics model and determining storage period at various temperatures. Porang chips were stored at a relative humidity (RH) of approximately 70% and temperatures of 15 ℃, 20 ℃, 25℃, and 30 ℃ for 90 days. The parameters measured were moisture content, hardness, density, color, glucomannan, and ash content. The rate of quality change in hardness and density of chips was analyzed using the kinetics model that was validated through the Arrhenius equation. After the validation test confirmed its accuracy, storage period was determined based on the hardness parameter. The measurement of porang chips parameters was analyzed using ANOVA with Duncan’s post hoc test to assess the effect of storage temperatures. The results showed that storage temperatures affected hardness and density parameters but did not affect the color, glucomannan, and ash content. The kinetics analysis of changes in hardness and density of porang chips followed a zero-order reaction, showing that higher storage temperatures produced larger rate constant values. Validation using the Arrhenius equation yielded the following equations for density Y = -5154.5 + 9.1773 and hardness Y = -2152.4 + 2.3371. The determination of shelf life for porang chips based on the hardness parameter resulted in values of 386, 345, 312, and 271 days at storage temperatures of 15 ℃, 20 ℃, 25 ℃, and 30 ℃, respectively.